2022
DOI: 10.3389/fphar.2022.829952
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Sildenafil and Ba2+ at a Low Concentration Show a Significant Synergistic Inhibition of Inward Rectifier Potassium Current Resulting in Action Potential Prolongation

Abstract: Sildenafil (Viagra) is a vasodilator mainly used in the treatment of erectile dysfunction. Atrial or ventricular fibrillation may rarely occur as a side effect during sildenafil therapy. Although changes in inward rectifier potassium currents including IK1 are known to contribute to the pathogenesis of fibrillation, the effect of sildenafil on IK1 has not been studied. In experiments, Ba2+ is used as a specific inhibitor of IK1 at high concentrations (usually 100 µM). Being an environmental contaminant, it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 41 publications
(48 reference statements)
4
7
0
Order By: Relevance
“…Arrhythmogenesis related to the use of sildenafil is likely complex. Besides the effect of sildenafil on the Kir channels demonstrated in this study as well as in our previous study (Macháček et al, 2022), changes of other cardiac ionic currents should be considered. A study on the rapid component of delayed rectifier potassium current (I Kr ) demonstrated that sildenafil exerted a reversible inhibitory effect on I Kr channels expressed in a cell line, but the inhibition was below 10% at the therapeutic sildenafil concentration of 1 µM (the half inhibitory concentration of ~100 µM); the supratherapeutic concentration (30 µM) inhibiting ~44% of I Kr in the cell line showed a prolongation cardiac repolarization by 15% in isolated guinea pig heart (Geelen et al, 2000).…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Arrhythmogenesis related to the use of sildenafil is likely complex. Besides the effect of sildenafil on the Kir channels demonstrated in this study as well as in our previous study (Macháček et al, 2022), changes of other cardiac ionic currents should be considered. A study on the rapid component of delayed rectifier potassium current (I Kr ) demonstrated that sildenafil exerted a reversible inhibitory effect on I Kr channels expressed in a cell line, but the inhibition was below 10% at the therapeutic sildenafil concentration of 1 µM (the half inhibitory concentration of ~100 µM); the supratherapeutic concentration (30 µM) inhibiting ~44% of I Kr in the cell line showed a prolongation cardiac repolarization by 15% in isolated guinea pig heart (Geelen et al, 2000).…”
Section: Discussionmentioning
confidence: 57%
“…The potentiation of the sildenafil inhibitory effect on Kir2.2 was observed only in the cells with low reactivity to Ba 2+ -induced inhibition (Figures 5A, B). On average, these changes were not significant because the inhibitory effect of Ba 2+ on Kir2.2 was too high, preventing the potentiation as has been also observed at higher Ba 2+ inhibition in our recent study on rat I K1 (Macháček et al, 2022). The inhibition of Kir2.2 induced by Ba 2+ was higher than that of Kir2.1 (at −110 mV: 24.5% ± 7.0% in Kir2.2 vs. 6.31% ± 1.34% in Kir2.1, n = 6, p < 0.01; at −50 mV: 16.0% ± 8.1% in Kir2.2 vs. 5.95% ± 0.75% in Kir2.1, n = 8, p > 0.05).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations